2019
DOI: 10.1177/0022042619872955
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the sale of prescription drugs and medicine on the AlphaBay cryptomarket

Abstract: Internet access has provided new ways to trade goods. Unlike conventional legal sale sites, cryptomarkets facilitate exchanges in a context where the anonymity of participants is warranted. The aim of this article was to obtain a better understanding of the trafficking of prescription drugs and medicine on the AlphaBay cryptomarket. The results showed that alprazolam, oxycodone, and Adderall were the most offered prescription drugs while alprazolam, diazepam, and oxycodone were the most sold substances. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The listed drugs are primarily for personal use or social networks including friends and colleagues, although most revenue comes from business-to-business dealings (Aldridge & Décary-Hétu, 2016; Barratt, 2012; Barratt et al, 2016; Demant et al, 2018). Some studies have investigated the geography of the vendors’ countries of origin and their destination countries, and revealed that cryptomarkets have primarily manifested in the Anglo-Saxon world and Western Europe (Christin, 2013; Demant et al, 2018; Dolliver, 2015; Morelato et al, 2020; Norbutas, 2018; Van Buskirk, Naicker, Roxburgh, Bruno, & Burns, 2016). The buyer-seller network is highly fragmented across geographical borders to reduce the risk of inspection (Aldridge & Askew, 2017; Broséus, Rhumorbarbe, Morelato, Staehli, & Rossy, 2017b; Kruithof et al, 2016; Norbutas, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The listed drugs are primarily for personal use or social networks including friends and colleagues, although most revenue comes from business-to-business dealings (Aldridge & Décary-Hétu, 2016; Barratt, 2012; Barratt et al, 2016; Demant et al, 2018). Some studies have investigated the geography of the vendors’ countries of origin and their destination countries, and revealed that cryptomarkets have primarily manifested in the Anglo-Saxon world and Western Europe (Christin, 2013; Demant et al, 2018; Dolliver, 2015; Morelato et al, 2020; Norbutas, 2018; Van Buskirk, Naicker, Roxburgh, Bruno, & Burns, 2016). The buyer-seller network is highly fragmented across geographical borders to reduce the risk of inspection (Aldridge & Askew, 2017; Broséus, Rhumorbarbe, Morelato, Staehli, & Rossy, 2017b; Kruithof et al, 2016; Norbutas, 2018).…”
Section: Introductionmentioning
confidence: 99%